Tyre Retreading - Banerjee, Bireswar (Walter de Gruyter GmbH, 2019)
This book describes the different elastomers utilized in tyre retreading. Among others, it discusses reinforcing fillers in terms of their efficacy, the use of bonding agents, and their relevance to the tyre retreading process. The authors give specific guidelines for the practical compounding of different rubber compounds to make retread. A practical approach is also taken to describing the manufacturing technology used in tyre retreading.- Resumé vydavatel